(untitled) (Psychology Travelogs, 2025)
The article presents the results of an empirical study of the level of professional competence of foreign language teachers in higher education institutions, which is necessary for the implementation of didactic techniques to ensure feedback and optimise the educational process. It considers the personal qualities that a teacher must possess in order to carry out relevant didactic actions with the aim of ensuring feedback and optimising the educational process. It shows the unevenness of the gradual formation of the subjectivity of a foreign language teacher. Theoretical comparison and analysis of empirical data on the development of professional competencies of foreign language teachers in a higher education institution that trains social work specialists, based on the eco-psychological model of subjectivity formation (OSS-B methodology) and expert assessment based on the SPC model, allowed us to hypothesise that the development of professional competencies in these teachers is in a certain correspondence with the eco-psychological stages of subjectivity formation. To confirm this assumption, the empirical data obtained were processed using discriminant analysis. Based on the structural coefficients of four discriminant functions, groups of foreign language teachers were identified that differ in their stages of subjectivity formation in relation to the stages of professional competence formation. The types of pedagogical activity and conditions under which the subjectivity of a foreign language teacher will develop optimally and the self-transformation of the subject will be realised are indicated. All this proves the validity of using the eco-psychological model of subjectivity formation as a theoretical construct for analysing and interpreting the development of professional competence using the example of foreign language teachers at higher education institutions who are involved in training future social work specialists.